Anggah-Ungguhing Basa Bali dalam Pembelajaran Drama di Kelas X SMK Negeri 3 Tabanan Tahun Pelajaran 2019/2020 - Ni Made Ari Tresnawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The skill of speaking in Balinese is closely related to the learning material of anggah-ungguhing basa Bali or sor singgih basa Bali. The use of Balinese language in vocational high schools can be taught through learning Balinese drama. The problems in this study are (1) the use of Balinese language in teaching drama in Class X SMK (Vocational High School) Negeri 3 Tabanan in the 2019/2020 academic year, (2) the obstacles faced in the use of Balinese language teaching in drama learning in the Class X SMK Negeri 3 Tabanan for the academic year 2019/2020, and (3) the strategies used to increase the use of Balinese language in teaching drama in Class X SMK Negeri 3 Tabanan for the academic year 2019/2020. This study concludes that in learning drama, students can use all types of anggah-ungguhing basa Bali, but there are still some errors in their use. Constraints experienced by students in the use of anggah - ungguhing basa Bali in drama learning are the lack of mastery of Balinese alus vocabulary, difficulty understanding characters in traditional Balinese drama scripts, and online learning systems. Learning strategies that can be used by teachers of Balinese language subjects in an effort to improve student's ability to understand the use of Balinese anggah - ungguhing basa in drama learning are innovative learning strategies that are integrated with elements of 21st century learning. The innovative learning strategies that can be developed by teachers including designing innovative learning, implementing innovative learning models, and utilizing digital learning.